Some specific elements of Albania’s atmospheric droughts - Gjoni Anira; Kucaj Enkelejda; Cela Gazmir; Bardhi Azem; Stafa Gentiana (E3S Web of Conferences)
This study investigates the phenomenon of drought in Albania through quantitative indicators, combining theoretical insights with practical analysis of drought durations, particularly in terms of consecutive decades with minimal rainfall. Drought, characterized by extended periods of precipitation deficiency and dry conditions, significantly disrupts the hydrological cycle, reduces soil moisture levels, alters temperatures, impacts water availability, and affects river flow rates. These factors contribute to environmental degradation, biodiversity loss, and substantial economic repercussions. Despite Albania’s compact size, its segmentation into 13 subzones and 4 distinct phytoclimatic regions reveals notable variability in climate characteristics and occurrences of extreme weather events, including drought. The country experiences a pronounced seasonality in rainfall, with the majority occurring between October and April, exacerbating dry conditions during summer months. Human activities such as deforestation and improper land management practices further exacerbate drought susceptibility. Approximately two-thirds of Albania’s land area comprises dry and semi-arid regions prone to drought and desertification. The study employs hydrothermal and xerothermic coefficients, alongside analysis of synoptic conditions conducive to drought, to systematically assess and compare drought occurrences across different regions within Albania. This research aims to enhance understanding of drought dynamics in Albania, informing strategies for effective mitigation and management of drought impacts in the region.